An investigation of claim management culture of highways road construction projects in Ghana. - Foli, Gabriel Ayi Quaye (KNUST, 2025)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the award of degree Master of Science in Project Management